SHORT-TERM MAGNESIUM OXIDE MONOHYDRATE TREATMENT IMPROVES LIPIDS AND INFLAMMATION IN HEALTHY SUBJECTS - Shechter, Michael; Saad, Tomer; Shechter, Alon; Matetzky, Shlomi (Journal of the American College of Cardiology, 2015)
Conclusion: Short-term oral magnesium oxide monohydrate treatment significantly improved total and LDL cholesterol and hs-CRP compared with magnesium citrate in healthy subjects with no apparent heart disease.